Big Data from the bottom up. Issue 2 (10th July 2014) - Couldry, Nick; Powell, Alison
This short article argues that an adequate response to the implications for governance raised by 'Big Data' requires much more attention to agency and reflexivity than theories of 'algorithmic power' have so far allowed. It develops this through two contrasting examples: the sociological study of social actors used of analytics to meet their own social ends (for example, by community organisations) and the study of actors' attempts to build an economy of information more open to civic intervention than the existing one (for example, in the environmental sphere). The article concludes with a consideration of the broader norms that might contextualise these empirical studies, and proposes that they can be understood in terms of the notion of voice, although the practical implementation of voice as a norm means that voice must sometimes be considered via the notion of transparency.